Exploring Malaysian public universities Japanese language students' views on the effects of LGBT elements in anime and manga - Paee, Rokiah; Abdul Rashid, Roswati; Ahmad, Normah; Mamat, Roslina (Sci and Tech Universal Inc, 2023)
Background and Purpose: Anime and manga have drawn a global audience and become popular in a wide range of genres, including in Malaysia. These two popular cultures occasionally include LGBT elements in their storylines. This article examines Malaysian university students' views on LGBT elements in anime and manga. The specific objectives were to (1) identify anime and manga that incorporate LGBT elements, which are consumed by university students in Malaysia, and (2) investigate their views on the effects of consuming these materials.